2009
DOI: 10.1093/ejo/cjp056
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulphate (WF6 epitope) levels in peri-miniscrew implant crevicular fluid during orthodontic loading

Abstract: The aim of this study was to monitor changes in chondroitin sulphate (CS; WF6 epitope) levels in peri-miniscrew implant crevicular fluid (PMICF) during orthodontic loading. Ten patients (seven males and three females; aged 22.0 +/- 3.4 years), who required orthodontic treatment with extraction of all four premolar teeth, participated in the study. Twenty miniscrew implants (used as orthodontic anchorage) were placed, two in each patient, buccally and bilaterally in the alveolar bone between the roots of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Various studies present in the literature attempt to assess the stability of miniscrews from different perspectives such as clinical [3,14,15], biomechanical [16-18], histological [15],[19-21], or biochemical. Several biochemical markers have been associated with inflammation and remodelling of peri-implant tissue around osseo-integrated dental implants [20-23], but only few studies were found in the literature in which biochemical assessments were used to investigate the stability of miniscrews [7],[24-26]. In the study by Sari and Ucar [7], IL-1β levels in PMCF were collected only after loading to determine the effects of mechanical stress on the miniscrews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies present in the literature attempt to assess the stability of miniscrews from different perspectives such as clinical [3,14,15], biomechanical [16-18], histological [15],[19-21], or biochemical. Several biochemical markers have been associated with inflammation and remodelling of peri-implant tissue around osseo-integrated dental implants [20-23], but only few studies were found in the literature in which biochemical assessments were used to investigate the stability of miniscrews [7],[24-26]. In the study by Sari and Ucar [7], IL-1β levels in PMCF were collected only after loading to determine the effects of mechanical stress on the miniscrews.…”
Section: Resultsmentioning
confidence: 99%
“…The mean IL-1β level in PMCF of healthy miniscrews did not increase significantly during orthodontic loading. Intachai et al [24] assessed medians of chondroitin sulphate levels in PMCF around ‘immobile’ miniscrews, between the unloaded and loaded periods, which were not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Bilateral maxillary posterior teeth were used for the measurement CS levels. The volume of GCF collected from the last 2.0 mm of each paper strip was 0.1  μ L [7]. Competitive ELISA with WF6 monoclonal antibody was used to detect CS levels in the collected GCF.…”
Section: Methodsmentioning
confidence: 99%
“…Orthodontic force causes considerable localized remodeling of the alveolar bone and brings about changes in the CS levels in GCF. Intachai et al [7] monitored changes in CS around immobile miniscrew implants, during the unloaded and loaded periods, and concluded that CS could be detected and might be used as biomarkers for assessing alveolar bone remodeling around miniscrew implants during orthodontic loading. Furthermore, our previous study [8, 9] reported increases in CS levels in GCF around orthodontically moved canines.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated levels of CS in GCF are apparently associated with four clinical parameters of periodontal status, which serve as gold standards for periodontal inflammation and destruction [ 14 ]. In addition to periodontal disease, CS levels can be precisely detected in physiologic tooth movement [ 26 , 27 ] and in patients with pathologic inflammatory disorders, such as degenerative joint diseases [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%